Intrinsic kinetics of interfacial polycondensation reactions– the reaction of mPDA with TMC. (1st December 2020) - Behera, Subhalaxmi; Akkihebbal, Suresh K.
Abstract: The performance of thin film composite membranes used in reverse osmosis is decided by the thickness and structure of the thin functional layer, which in turn depend on the kinetics of the interfacial polycondensation (IP) reaction which produces this layer. Quantitative determination of these kinetics has been a challenge. In the present study, we extend the method of pH-metry developed in our earlier work to the study of IP kinetics, in the presence of the side reaction of hydrolysis of the organic phase monomer. The method has been used to establish the kinetics of MPDA –TMC system in the presence and absence of a surfactant, Tween-85. The experimental method used eliminates all transport resistances, so that intrinsic kinetic control of the observed process is ensured. The hydrolysis reaction is studied separately by an adaptation of the same method, and those kinetics are systematically incorporated in the treatment of the data from the IP reaction. The observed kinetics have been fitted to a lumped kinetic form of the power law type, and show that the reaction is approximately first order in the acid chloride group concentration, and order 1.6 in the amine group concentration. The surfactant has been seen to influence the magnitude of the rate constant significantly. The reaction usually stops well short of 100% conversion of the stoichiometrically limiting monomer, because of the lowering of pH which restricts the availability of the aqueous phase monomer at the reaction locale. Graphical abstract: Image 1 Highlights: Proposed method uses a fast pH measurement to obtain kinetic data. Protocols developed that ensure kinetic control during reaction. Hydrolysis side reaction systematically accounted for in interpreting kinetic data. m -PDA—TMC reaction is first order in acid chloride and order 1.6 in amine. Surfactant has a significant accelerating influence on the kinetics.